A study of postgraduate students in an Astrophysics bridging year: identifying contradictions in a complex system - Nwosu, Victoria (Department of Physics, 2014)
Astronomy and Astrophysics have been designated one of the flagship areas of research in South Africa. As part of human capacity building in this regard, a postgraduate national teaching programme at the Honours and Masters level, the National Astrophysics and Space Science Programme (NASSP) was established by an interested of group universities and located at the University of Cape Town. Despite initial success the programme failed to recruit and retain black South African students. In order to address this problem a postgraduate bridging program, the Extended Honours Programme (EHP), was established as a one year pre-honours level educational intervention. The research described in this thesis is directed at trying to identify the nature of the problems faced by the EHP students during their transition from their previous institutions to UCT. The Cultural Historical Activity Theory (CHAT) framework and its principle of contradictions and multivoiceness are employed to describe the NASSP as an activity system. According to the CHAT framework an activity system may experience four types of contradictions: primary, secondary, tertiary and quaternary. These four types of contradictions were identified and located within, and between, the components of the activity system. The major primary contradiction identified was in the ""double nature"" of the programme, essentially, a double bind between conceptual understanding and getting good grades. Several secondary contradictions, tertiary contradictions and historical disturbances were also identified. Other disturbances which did not map into any of the four established contradictions are also highlighted. The methodology was further applied at the level of a single course where micro and macro tensions were detected in a key component of the EHP curriculum that had previously been identified as extremely challenging, namely, the intermediate level electromagnetism course. To this end this specific activity system was interrogated and inherent tensions including historical and systemic tensions were identified. These historical and systemic tensions were noted to create disturbances such as poor conceptualization of physical problems, mismatches in students' and lecturers' expectations and unproductive learning strategies.